Developing an app proposal for tuk tuk service management - Perdigão, E.; Alturas, B. (International Journal of Business Information Systems, 2025)
In most tuk tuk companies, outdated methods are used in the daily management of the company, which makes the processes slow and time-consuming. So, it was found that it was necessary to use information technologies to make tuk tuk companies more effective in daily management. Therefore, the main objective of this project was the development of an application, that works like an information system, for tuk tuk companies. The requirement gathering carried out, allowed conclusions to be reached about the type of information that was to be relevant in the application as well as its functionalities. It was concluded that it is necessary to have two types of applications, a mobile and a desktop. The App brings advantages related to the reduction of errors in the database, overview and knowledge of the employees’ work, and improvement in time management that can increase the productivity of the company’s managers.